IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI EKSTRAKURIKULER PRAMUKA - Musrianah Musrianah; Ghufron Abdullah; Ngurah Ayu Nyoman Murniati (Universitas Muria Kudus, 2022)
This research aims to describe the Implementation of Character Education through Scout Extracurriculars at SD Negeri Pringapus 03 Kecamatan Pringapus Kabupaten Semarang. This research is a qualitative phenomenology research.Â The subjects of the study were the principal, teacher, students, parents, and school committee.Â The object of research is a social situation that shows the implementation of character education through scouting extracurricular including planning, implementation, and supervision. Data collection techniques use observation, interviews, and documentation. Qualitative data analysis techniques using Miles and Huberman's interactive models include data collection, data reduction, data presentation, and inference. Validity test using source triangulation. The results showed that the implementation of character education through scout extracurriculars was carried out well, as evidenced by activities: (1) character-education planning through scout extracurriculars has been implemented by involving related parties in providing consideration and input, (2) implementation is realized by various policies and activity programs, (3) supervision is carried out regularly in and discussed in monthly meetings, semesters, and end of the yearÂ